Feeding 3-nitrooxypropanol reduces methane emissions by feedlot cattle on tropical conditions - Araújo, Tiago L. R [UNESP]; Rabelo, Carlos H. S; Cardoso, Abmael S [UNESP]; Carvalho, Victor V; Acedo, Tiago S; Tamassia, Luis F. M; Vasconcelos, Guilherme S. F. M; Duval, Stephane M; Kindermann, Maik; Gouvea, Vinicius N; Fernandes, Marcia H. M. R [UNESP]; Reis, Ricardo A [UNESP] (Oxford University Press (OUP), 2023)
Our objective was to evaluate the effects of feeding 3-nitrooxypropanol (3-NOP; Bovaer, DSM Nutritional Products) at two levels on methane emissions, nitrogen balance, and performance by feedlot cattle. In experiment 1, a total of 138 Nellore bulls (initial body weight, 360 ± 37.3 kg) were housed in pens (27 pens with either 4 or 5 bulls per pen) and fed a high-concentrate diet for 96 d, containing 1) no addition of 3-NOP (control), 2) inclusion of 3-NOP at 100 mg/kg dry matter (DM), and 3) inclusion of 3-NOP at 150 mg/kg DM. No adverse effects of 3-NOP were observed on DM intake (DMI), animal performance, and gain:feed (P > 0.05). In addition, there was no effect (P > 0.05) of 3-NOP on carcass characteristics (subcutaneous fat thickness and rib eye area). In experiment 2, 24 bulls (initial BW, 366 ± 39.6 kg) housed in 12 pens (2 bulls/pen) from experiment 1 were used for CH4 measurements and nitrogen balance. Irrespective of the level, 3-NOP consistently decreased (P < 0.001) animals' CH4 emissions (g/d; ~49.3%), CH4 yield (CH4/DMI; ~40.7%) and CH4 intensity (CH4/average daily gain; ~38.6%). Moreover, 3-NOP significantly reduced the gross energy intake lost as CH4 by 42.5% (P < 0.001). The N retention: N intake ratio was not affected by 3-NOP (P = 0.19). We conclude that feeding 3-NOP is an effective strategy to reduce methane emissions, with no impairment on feedlot cattle performance.
Keywords: 3-nitrooxypropanol; beef cattle; greenhouse gases; sustainability